‘Let me be a bad example to you’ : navigating desire and freedom through an analysis of carol aird’s discourse in patricia highsmith’s the price of salt - Luz, Eduarda Pacheco da (2025)
Patricia Highsmith’s The Price of Salt, later reissued as Carol, is recognised by its groundbreaking influence in queer American literature for rather exclusively presenting an openly lesbian story with a hopeful and positive conclusion for its two main characters, Carol Aird and Therese Belivet, who fall in love amidst the throes of Carol’s divorce from a loveless marriage. Initially published under the pseudonym Claire Morgan, the novel defied morality conventions and literary patterns upon its original release in 1952. While the story has been widely analysed through the lens of queer theory, having its overt lesbian thematic discussed recurrently, much of the academic archive surrounding the novel remains surface-level in terms of character analysis or theoretical literary insights, often reducing its richness to its depiction of homosexuality alone. Therefore, this dissertation proposes an analysis of Carol Aird’s character, seeking to explore how her discourse articulates desire, freedom and female empowerment in a historical context of repression of women’s homosexuality in the United States in the 1950s. It also intends an assessment of how the narrative, constructed by a third-person narrator who only reproduces Therese’s perspective, influences the reader in their reception of Carol Aird, limiting them to a partial, ambiguous, and often imprecise view of her. Structured in three chapters, this study begins by situating the novel within the cultural and political scenario of 1950s America, emphasising and illustrating the moral hysteria of the post-war and McCarthy era with the help of Fried (1990) and Johnson (2004), who draw the historical panorama, in addition to Beauvoir (1956), Rich (1980), Foucault (1990), and Keller (2005), who establish the relation between the political climate and the matters of sexuality. Understanding that Carol’s expression is subdued by a partial narrator that favours Therese’s perspective, the second chapter uses Kuhns (1972) to establish the concept of the average and competent reader and essentially concerns itself with narrative theory sustained by Booth (1983), exploring and exemplifying how the third-person limited narrator must be detached from Therese’s point of view for a more intricate assessment of the novel, as it both shapes and distorts the average reader’s understanding of Carol. The final chapter is based on an authorial interpretation of Carol’s actions, dialogue, and nonverbal cues, supported by Davidhizar (1992), Duke (1974), and Villoro (2017), as it attempts to elucidate Carol’s nuanced psychological and emotional profile and how it breathes life into the story. Ultimately, this study defends that Carol Aird stands as the emotional force and legacy of the novel, arguing that shifting the focus of The Price of Salt from sexuality to character debate gives emphasis on the novel as a work of literary depth and emotional and psychological complexity that demands and deserves critical attention beyond its queer context and that is essentially anchored by the force, the bravery, and the boldness of Carol Aird.